(untitled) (Bangladesh Journal of Medical Microbiology, 2024)
Background: Multi-drug-resistant (MDR) strains of Enterobacter cloacae are becoming increasingly prevalent worldwide, which is reducing treatment options. Objective: The purpose of the present study was to evaluate protective antibody response following vaccination with formaldehyde inactivated Enterobacter cloacae. Methodology: The study used formaldehyde inactivated MDR Enterobacter cloacae obtained from various clinical samples to immunize 10 Swiss albino mice through intradermal injection. After the third dose of immunization, the mice were challenged with live Enterobacter cloacae through intraperitoneal injection and were monitored for 14 days. Blood was collected from the tail 7 days after each booster and through cardiac puncture 14 days after the challenge. The serum antibody produced by the vaccine was evaluated for bactericidal activity and antigen-binding capacity using ELISA. Results: In this study, it was observed that 100% of the immunized mice survived after 14 days of challenge. The ELISA showed that all the immunized mouse sera had 100% bactericidal activity. Additionally, all the pre- and post-challenge immunized serum immunoglobulin G antibodies had significantly higher optical density values compared to the control mice in ELISA. Top of Form Conclusion: Our study showed that when formaldehyde inactivated MDR Enterobacter cloacae was used for intradermal immunization in Swiss albino mice, it produced antibodies that offered protection. Using a first-generation vaccine can provide a larger pool of antigens to elicit the desired immune response. Bangladesh Journal of Medical Microbiology, January 2024;18(1):44-49